(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article brings a report of the teaching experience in online platforms for students of Elementary School II in the city of Sorocaba, SP, carried out during the Covid-19 pandemic in 2020-21. An adaptation was made, for the virtual environment, of the theatrical games present in Viola Spolin’s binder. The experience instigated the proposition of a virtual theatrical production, entitled "My window opened to the square", accepted to be developed in the 20th FETO - Student Theater Festival of Belo Horizonte, MG. The article explains the methodology and results of the process with the students, considering the procedures from the perspective of active learning, and considering the remote environment as a structuring device of language.